MANAJEMEN PENGEMBANGAN KURIKULUM BERBASIS KEBUTUHAN PENDIDIKAN - Bintang Furmayanti; Aras; Muh. Reza Setiawan; Sulkifli (Wasīlah: Journal Of Sharia Sciences, 2026)
This study discusses curriculum development based on educational needs as an effort to improve the quality of learning in schools. Curriculum has an important role in the educational process because it serves as a guideline in implementing teaching and learning activities. Therefore, curriculum development needs to be adjusted to the needs of students, educational developments, and school environmental conditions. This study uses a qualitative approach by collecting data through observation, interviews, and documentation. Curriculum development is carried out through planning, implementation, and evaluation processes involving schools and educators. A curriculum designed based on educational needs can help create a more effective, directed, and appropriate learning process in accordance with students’ development.